Pudendal nerve versus Lower Limb nerves electrophysiological abnormalities in diabetics with erectile dysfunction in Baghdad - Mohammed J. Al-Hadeethi; Najeeb H. Mohammed (مجلة كلية الطب, 2023)
Background: Erectile dysfunction (ED) is the persistent inability to perform and maintain penile erection strong enough for fulfilling sexual interaction. It is caused by autonomic neuropathy, vasculogenic causes, endocrine deficit, drug-induced, psychosocial problems, or a combination of these causes.